From hotspots to hope: Unearthing gender narratives in climate-touched terrains - CGIAR GENDER Impact Platform (CGIAR GENDER Impact Platform, 2023)
The objective of the session is bringing together key pieces of primary research on gender equality in transforming agri-food systems in the face of climate change, conducted in the framework of a collaboration between IDRC, the GENDER Impact Platform, and CGIAR and external partners. A research program was set up to identify pathways in changing food systems that allow for increasing gender equality. Climate change emerged as a significant and critical trend, simultaneously affecting agri-food systems and gender equality; hence this research focuses on the intersection of climate change, agri-food systems and gender equality. The conceptual framework builds on the gendered food systems frameworks, as well as recent frameworks linking climate change and gender equality in agri-food systems. The session will briefly introduce how we identified climate–agriculture–gender inequality hotspots. The session will include two presentations of results of in-depth case studies examining the intersections of climate change, gender equality and agri-food systems in such hotspots, more particularly in Bangladesh and Zambia. This will be followed by two presentations of results of quasi-experimental impact studies testing the potential of interventions to address gender equality in food systems and in climate resilience in these hotspots. A representative of IDRC will attend, reflecting on the overarching learning and implications for gender equality and climate action in interventions.